2020
DOI: 10.1140/epjp/s13360-020-00322-x
|View full text |Cite
|
Sign up to set email alerts
|

Weak gravitational lensing by stringy black holes

Abstract: In this paper, we discuss the weak gravitational lensing in the context of stringy black holes. Initially, we examine the deflection angle of photon by charged stringy black hole. For this desire, we compute the Gaussian optical curvature and implement the Gauss-Bonnet theorem to investigate the deflection angle for spherically balanced spacetime of stringy black hole. We also analyze the influence of plasma medium in the weak gravitational lensing for stringy black hole. Moreover, the graphical impact of impa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
3

Relationship

6
4

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 84 publications
1
11
0
Order By: Relevance
“…where we used Eqs. (27) and (28). This result is the same as that calculated by α ≡ Ψ R − Ψ S + φ RS in Ref.…”
Section: Examples In Asymptotically Non-flat Spacetimessupporting
confidence: 89%
“…where we used Eqs. (27) and (28). This result is the same as that calculated by α ≡ Ψ R − Ψ S + φ RS in Ref.…”
Section: Examples In Asymptotically Non-flat Spacetimessupporting
confidence: 89%
“…The weak deflection angle, using the GBT for various spacetimes, was studied by many physicists. For example, the deflection angle of light was studied for BHs and wormholes by the following authors [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]: Ovgun et al studied for different spacetimes, such as Schwarzschild-like spacetime, the bumblebee gravity model [54][55][56][57][58][59][60], and Javed et al studied the impact of various matter fields [61][62][63][64][65]. Next, Ishihara et al [66] showed that it is conceivable to calculate the weak deflection angle using the finite-distances method.…”
Section: Kdsmentioning
confidence: 99%
“…Then, Crisnejo and Gallo showed that the plasma medium deflects photons [41]. For more recent works, one can see [42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82].…”
Section: Introductionmentioning
confidence: 99%